Immunogenicity characterization of genetically fused or chemically conjugated heat-stable toxin toxoids of enterotoxigenic Escherichia coli in mice and pigs. Issue 4 (17th February 2019) - Seo, Hyesuk; Lu, Ti; Nandre, Rahul M; Duan, Qiangde; Zhang, Weiping
ABSTRACT: Enterotoxigenic Escherichia coli (ETEC) producing type Ib heat-stable toxin (STa) are a main cause of children's diarrhea and travelers' diarrhea, thus STa needs to be targeted in ETEC vaccine development. However, because this 19-amino acid STa is poorly immunogenic, attempts to genetically fuse or chemically couple it to carrier proteins have been made to enhance STa immunogenicity. In this study, we selected one genetic fusion and one chemical conjugate to comparatively evaluate STa immunogenicity. The genetic fusion is 3xSTaN12S -mnLTR192G/L211A carrying three toxoid (STaN12S ) genetically fused to a double mutant LT monomer (mnLTR192G/L211A ); the chemical conjugate is BSA-STaA14T, which has toxoid STaA14T chemically coupled to bovine serum albumin (BSA). We immunized mice with the STa toxoid fusion and chemical conjugates, and examined antibody responses. Furthermore, we immunized pigs and evaluated derived antibodies for efficacy to passively provide protection against ETEC diarrhea using a piglet model. Data showed that mice subcutaneously immunized with BSA-STaA14T or 3xSTaN12S -mnLTR192G/L211A developed a strong anti-STa antibody, and the induced antibodies exhibited equivalent toxin-neutralizing activities. Pigs immunized with 3xSTaN12S -mnLTR192G/L211A or BSA-STaA14T developed similar levels of anti-STa antibodies; piglets with passively acquired antibodies induced by the genetic fusion appeared better protected against STa + ETEC. Results from the current study indicate that the fusion and conjugate approaches are viable options for facilitating STa immunogenicity and developing ETEC vaccines. Abstract : The immunogenicity of two antigen strategies, genetic fusion and chemical conjugation from STa, were comparatively investigated to prepare safe and immunogenic STa antigens for ETEC vaccine development.